11.7k views
0 votes
Simplify the expression where possible. (r⁻³s²t)⁴

User OrangeRind
by
5.5k points

2 Answers

6 votes

Simplify the expression where possible. (r⁻³s²t)⁴

answer= r^-12 s^8 t^4

User Satyen
by
5.2k points
6 votes

Answer:
(s^8t^4)/(r^(12))

Explanation:

By the Negative exponent rule, you know that:


a^(-1)=(1)/(a)

And by the Power of a power property, you also know the following:


(a^m)^n=a^(mn)

Therefore, applying the above, you can simplify the given expression
(r^(-3)s^2t)^4. Then you get:


(r^(-3)s^2t)^4=r^(-12)s^8t^4 =(s^8t^4)/(r^(12))

User Warren Nocos
by
5.8k points